Process Improvement Through Learning About Build Size Model Cooperative Stad And Quiz In Class Vi Sdn 33 Desert Long District Of Koto Xi Tarusan In Subjects Mathematics Academic Year 2016/2017 - Afriyenti Afriyenti (Jurnal Ilmiah Pendidikan Scholastic, 2017)
Learning Mathematics presented with lectures and exercises individually often disliked by the students. As a result of learning outcomes is always to the bottom than the other subjects. Though the science of mathematics has a very strategic role in many lives. To create a learning process a fun, exciting and can improve learning outcomes, it is necessary to change an interesting learning that implement cooperative learning model of STAD and quizzes. The formulation of the problem posed: (1) How STAD cooperative learning models to encourage students to learn about the broad wake up more excited? (2) How to play a quiz to encourage students to learn about the broad wake become more vibrant?. To answer the formulation of the problem, then do research on the subject of 26 students of SD Negeri 33 Desert Long District of Koto XI Tarusan in the academic year 2016/2017 in the sixth grade. Retrieving data using observations, questionnaires, written tests and deeds, as well as documentation. The study was conducted by three cycles. Each cycle is done planning, action, observation, and reflection. Implementation of the action in a sequence as follows: classical learning, group learning to create questions and answers STAD model, and quizzes. Each cycle consists of two meetings. The first meeting of classical learning, group work, and the performance of the group in the form of a quiz. Meeting II continued performance of the group in the activities of the quiz and evaluation of learning outcomes. The results of the study in the first cycle, classical learning activities only reached 54.22%. It has not reached the expected improvement of the learning process that is 60-70%. But in the learning process the group has reached 91.66% with a target of 70-80%, and quizzes reached 74.82% with a target of 70-80%. While the study results only reached 66.66% of students achieving a score of 60 -> 60 with a mean value of 65 while the specified target 100% completion reached a value of 60 -> 60. To improve learning classical at the second cycle each student is given some props Flat to be formed into a variety of joint-downs in making matter. In the second cycle an increase in the learning process to 66.15% classical because it started there were 4 students and 20 students ask recorded, in which the first cycle no student who asks questions and take notes. Learning Process group increased to 92.85%. Learning quiz and increased to 86.16%. While the learning outcomes reached an average 72.3%, with 76.92% of students reached 60 -> 60. In the process of delivering a matter of quiz show questions raised student is quite complicated, because of the form of various combinations of Flat are manifold. In Cycle III in addition there are props for each student,to be able to find comprehensive formula geometrical Flat broad based formula that has been dominated student, also coupled with the provision of a homework assignment in the form of exercises. This is due to the competencies to be mastered more difficult. An increase in the third cycle of classical learning process that is high enough into 84.61%. This is due to the increasing number of students who ask questions as many as 10 students and recorded as many as 26 students. Learning Process group increased become 97.61%, and the quiz activity increased to 92.77%.An increase in the third cycle of classical learning process that is high enough into 84.61%. This is due to the increasing number of students who ask questions as many as 10 students and recorded as many as 26 students. Learning Process group increased become 97.61%, and the quiz activity increased to 92.77%.An increase in the third cycle of classical learning process that is high enough into 84.61%. This is due to the increasing number of students who ask questions as many as 10 students and recorded as many as 26 students. Learning Process group increased become 97.61%, and the quiz activity increased to 92.77%. While learning outcomes reached an average 79.61% to 100% of students achieving a score of 60 -> 60. Thus all of the target has been reached. Based on the results of this study concluded (1) STAD cooperative learning models to encourage students to learn about the broad wake up excited, improve learning, and learning outcomes. (2) play a quiz to encourage students to learn about the broad wake become more vibrant, improve learning, and learning outcomes. Therefore advised that (1) To the teachers, to enhance the learning process and learning outcomes of mathematics, can use the cooperative model STAD as an option to overcome the problems of mathematics. (2) The learning strategy quizzes like in this study can also be applied in the study of mathematics, but necessary preparation, especially when the votes needed help answering group of students who are good to help teachers do the questions made by his friend. (3) For researchers who want to conduct further research in accordance with the study also suggested that making a more perfect preparation, especially in preparing the instruments and their observation rubrics clear at the time of the quiz activities. Also suggested that the observer team of at least two people,because according to the experience of the observer team of researchers are very busy in assessing the current activities of the quiz.